ISTILAH KEKERABATAN DALAM MASYARAKAT BAHASA MAKIAN TIMUR - Yakub, Arif; Abasa, Rafik M. (EDUKASI, 2016)
This research is making use of descriptive qualitative method. The data are collected with the method of Sudaryanto (1993) that is listening and interviewing method, make use the technique of free listening and interviewing with a list of questionaire. This research makes use the theory of Burning (1970) and Koentjaraningrat (1980) to answer the first problem, and of Spradley (1979) and Casson (1981) to the second one. The result of this research shows that the consanguinal kinship terms are Baba (father), Tou (grandfather), Wos (ego’s father), Galawewe (father of ego’s grandfather), Karekare ( grandfather of Ego’s grandfather), Baay (ego’s mother), Nene (mother’s mother), Nenewos (mother of nene), Nenegalawewe (mother of nenewos), Nenekarekare (mother nenegalawewe). Nikmapin (wife of masculine ego), Nikmon (husband of feminine ego), Tamno (ego’s elder brother),  Thano (ego’s younger brother), Damo 1 (ego’s sister), Damo 2 (ego’s brother), Mtu (ego’s child), Bbu (ego’s grandchild), Bbuwos (child of ego’s grandchild), Bbugalawewe (grandchild of ego’s grandchild), Bbukarekare (buyut dari ego). Afinal kinship terms: Nikmon (husband), Nikmapin (wife), Tafu (brother in-law), Hono (sister in-law), Iho (in-laws), Akmomon (wife’s father), Akmomapin (wife’s mother), Haliha (mother/father in-laws), Kanglolo (elder brother of father or mother), Kangkutu (younger brother of father or mother), Baaylolo (mother’s elder sister), Jojo (mother’s younger sister). Other kinship terms include: Jau (Allah), Kakang (guru ngaji), Engku (masculine teacher), Encik (feminine teacher). Keywords: kindship terms of East Makian language